Pengaruh Perlambatan Ekonomi Global dan Kinerja Keuangan Bank terhadap Pengembalian Saham Bank-Bank Komersial di Bursa Efek Indonesia - Acik Agfiyani; Serly Serly (Global Financial Accounting Journal, 2019)
This study aims to determine the effect of global economic slowdown and bank financial performance on the return of shares of commercial banks on the IDX. The independent variables used are NIM, NPL, CAR, LDR, Indonesian GDP, Chinese GDP, and American GDP. This study uses a sample of 31 commercial banks listed on the IDX in the period 2013-2017. The results of the study state that China's GDP and NPL have a positive effect on stock returns. The independent variable of American GDP has a negative effect on stock returns. Whereas NIM, CAR, LDR, and Indonesian GDP are declared not to affect stock returns.